Dietary verbena officinalis reduces feather-pecking duration in laying ducks by modulating cecal microbiota composition and hypothalamic neurotransmitter secretion - Ai Liu; Ai Liu; Ai Liu; Yongcai Zhu; Yongcai Zhu; Shenglin Yang; Shenglin Yang; Bingnong Yao; Bingnong Yao; Fuyou Liao; Fuyou Liao; Baoguo Zhu; et al. (Frontiers in Microbiology)
Verbena officinalis, a traditional Chinese herb with antioxidant and anti-inflammatory properties, has not been extensively studied for its effects on poultry gut microbiota and behavior. This study evaluated the impact of verbena officinalis supplementation (0, 2, and 4%) on growth performance, cecal microbiota, and feather-pecking behavior in laying ducks. Ninety healthy 1-day-old ducks were randomly assigned to three dietary treatments for a 5-week growth trial, and 45 feather-pecking ducks were used to assess the behavioral and neurochemical effects. Before the trials, ducks were adapted to the experimental conditions for 7 days and fed a basal diet. The results showed no significant differences in body weight or average daily gain (ADG) among the groups (p > 0.05), but the feed conversion ratio (FCR) was significantly lower in verbena groups (p < 0.05). Cecal microbiota analysis revealed higher Chao 1 and ACE indices (p < 0.01), increased Bacteroidetes (p < 0.05), and decreased Firmicutes and Megamonas in the verbena groups (p < 0.05). Spirochaetae (p = 0.014), Elusimicrobia (p = 0.032), and Lentisphaera (p = 0.036) were the predominant differential phyla, whereas Oscillospira (p = 0.003), Phascolarctobacterium (p = 0.039), and Megamonas (p < 0.001) were the predominant differential genera. Feather-pecking duration and hypothalamic norepinephrine (NE) levels were reduced in verbena groups (p < 0.05), with NE negatively correlated with Spirochaetae (p < 0.05). In conclusion, 2% verbena officinalis supplementation promotes beneficial gut microbiota changes and reduces feather-pecking behavior, although the underlying mechanisms require further investigation.